The sequential association between school bullying and oral health related quality of life (OHRQoL) in Chinese children and adolescents - Sifan Wang; Jin Lu; Guiqing Zheng; Yandie He; Shuqing Liu; Yi Xiang; Xinyi Liu; Xiang Wang; Yuanyuan Xiao; Ni Zhou (BMC Public Health)
Abstract Background School bullying has negative impacts on the overall health of children and adolescents, but the association between bullying and oral health-related quality of life (OHRQoL) is still unclear. Methods In this study, a two-wave prospective design was used to collect data in Yunnan Province, southwest China. A total of 5,346 children and adolescents aged 10–17 years were included in the study through two-stage randomized cluster sampling. Univariate and multivariate logistic regression models were employed to assess the sequential associations between baseline bullying and the subsequent OHRQoL. Stratified analyses were further performed to evaluate the effect modification by important demographic variables. Results The prevalence of school bullying was 16.40%. After adjustment, bullying involvement at baseline was associated with increased odds of subsequent poor OHRQoL (odds ratio, OR: 1.77, 95% CI: 1.50–2.11). Victims and bully-victims were seen significantly deteriorated OHRQoL, with ORs of 1.81 (95% CI: 1.50–2.19) and 2.10 (95% CI: 1.35–3.33). For different types of bullying victimization, only verbal victimization displayed a significant association with OHRQoL (OR: 2.07; 95% CI: 1.63–2.65). Bullying involvement was significantly associated with all four subdomains of OHRQoL, particularly for social well-being (OR: 1.91, 95% CI: 1.60–2.27). Stratified analyses revealed prominent effect modification by age, sex, ethnicity, and left-behind status in bullying-OHRQoL association. Conclusion Our findings suggest that children and adolescents who experienced school bullying had a significantly higher risk of subsequently poor OHRQoL, particularly for verbal victims. Targeted interventions should be designed and implemented.